The Use of Storytelling to Enhance English Listening Skills among Elementary School Students (International Journal of Education and Literature, 2026)
English learning at the elementary school level plays an important role in developing students’ early language competence, particularly in listening skills as the foundation for other language abilities. However, many learning processes still rely on conventional teaching methods that do not fully accommodate the developmental characteristics of young learners, resulting in limited engagement and listening comprehension. Therefore, this study aims to analyze the role of storytelling in improving English listening skills among elementary school students and to identify effective implementation strategies in classroom learning. This research employs a library research method by reviewing and analyzing various relevant literature sources, including books, scientific journals, and previous research findings related to storytelling in English language learning. The analysis shows that storytelling contributes significantly to improving students’ listening comprehension, vocabulary acquisition, attention, and learning motivation. Through structured narratives, expressive delivery, and the support of visual media, storytelling creates a contextual and meaningful learning environment that helps students understand spoken English more effectively. The findings also indicate that the effectiveness of storytelling is closely related to the developmental characteristics of elementary school students who learn better through concrete, imaginative, and engaging experiences. Furthermore, the implementation of storytelling through systematic stages pre-listening, while-listening, and post-listening can enhance students participation and comprehension during the learning process. In conclusion, storytelling can be considered an effective instructional strategy for improving English listening skills among elementary school students while also supporting vocabulary development and creating an engaging learning atmosphere.